Medicinal Plants and Phytochemicals for the Treatment of Pulmonary Hypertension - Jasemi, Seyed Vahid; Khazaei, Hosna; Aneva, Ina Yosifova; Farzaei, Mohammad Hosein; Echeverría, Javier (Frontiers in Pharmacology, 2020)
Background: Pulmonary hypertension (PH) is a progressive disease that is associated with pulmonary arteries remodeling, right ventricle hypertrophy, right ventricular failure and finally death. The present study aims to review the medicinal plants and phytochemicals used for PH treatment in the period of 1994 – 2019. Methods: PubMed, Cochrane and Scopus were searched based on pulmonary hypertension, plant and phytochemical keywords from August 23, 2019. All articles that matched the study based on title and abstract were collected, non-English, repetitive and review studies were excluded. Results: Finally 41 studies remained from a total of 1290. The results show that many chemical treatments considered to this disease are ineffective in the long period because they have a controlling role, not a therapeutic one. On the other hand, plants and phytochemicals could be more effective due to their action on many mechanisms that cause the progression of PH. Conclusion: Studies have shown that herbs and phytochemicals used to treat PH do their effects from six mechanisms. These mechanisms include antiproliferative, antioxidant, antivascular remodeling, anti-inflammatory, vasodilatory and apoptosis inducing actions. According to the present study, many of these medicinal plants and phytochemicals can have effects that are more therapeutic than chemical drugs if used appropriately.